Amyloid fibril formation by casein and fatty acid composition in breast milk of mastitis patients. Issue 8 (5th April 2022) - Liu, Jihua; Wang, Jia; Xu, Wenhui; Zeng, Lei; Wang, Chunyu; An, Yang; Tian, Huimin; Zeng, Baohua; Dong, Qinghai; Ji, Ye; Gao, Xiaojun; Du, Guangguang; et al.
Abstract: Mastitis can cause changes in the nutrient composition of breast milk, which may be harmful to both newborns and lactating mothers. In this study we preliminarily evaluated amyloid fibrils formation by casein and fatty acids (FA), as well as their potential relation with each other in the breast milk of mastitis patients. Six healthy volunteers and six mastitis patients were recruited from the Maternal and Child Health Care Hospital in Changchun were enrolled. Amyloid fibril content was assessed by thioflavin T fluorescence analysis, transmission electron microscope, circular dichroism, and proton nuclear magnetic resonance. FA contents were measured by gas chromatography. Healthy breast milk contained no amyloid fibrils but inflammatory breast milk did. Several FAs (hendecanoic acid, myristolenic acid, pentadecenoic acid, eicosatrienoic acid) differed significantly between the two groups ( p  < .05). The concentrations of the eicosatrienoic acid and eleven carbonic acids in the inflammatory groups were lower than those in the healthy groups, but the myristolenic acid and pentadecenoic acid were the opposite trend. Early detection of amyloid fibrils should be performed in lactating mothers with mastitis. Changes in FAs may reflect the importance of abnormal metabolism in amyloid fibril formation. Practical applications: The work preliminarily clarified the relationship between inflammation, fibril content, and fatty acid (FA) composition in breast milk. Healthy milk contained no amyloid fibril formed by casein but the inflammatory milk did. FAs were also significantly different between the two groups. Thus, an early determination of amyloid fibrils in milk should be considered for lactating women with mastitis to avoid the further malignant development. Additionally, the changes in FAs may reflect the importance of abnormal metabolism and oxidative pathways in amyloid fibril formation in the breast. Therefore, this study provided foundations for further investigation on the association between inflammation, fibril content and FA composition in breast milk. Abstract : Amyloid fibril in healthy and inflammatory breast milk from women investigated. Healthy milk contained no amyloid fibrils but inflammatory milk did. Fatty acids were significantly different between the two groups. Results clarified the relationship between inflammation, fibrils, and FA in breast milk.